Redescriptions of four species of Otobothrium Linton, 1890 (Cestoda: Trypanorhyncha), including new records from Australia, New Caledonia and Malaysia, with the description of O. parvum n. sp. - Beveridge, Ian; Justine, Jean-Lou (Zootaxa, 2007)
Redescriptions are provided of Otobothrium carcharidis (Shipley & Hornell, 1906), O. crenacolle Linton, 1890, O. curtum (Linton, 1909) and O. propecysticum Dollfus, 1969 based on the type specimens and new material collected from elasmobranch hosts from Australia, Malaysia and New Caledonia. All are considered to be valid species. A neotype has been designated for O. crenacolle. A new species, O. parvum, is described from the spiral valve of Carcharhinus amblyrhynchos (Bleeker, 1856) and Triaenodon obesus (Rüppell, 1837) from New Caledonia. Otobothrium minutum Subhapradha, 1955 is considered to be a valid but poorly described species, being differentiated on the basis of a lack of testes posterior to the ovary. Otobothrium cysticum (Meyer, 1842) is considered a species inquirenda. The presence of an hermaphroditic sac is a new character for the genus while O. curtum lacks bothrial pits, a characteristic found in all congeners examined. The species described or redescribed here can be distinguished based on the number of segments and the number and distribution of testes, in addition to the features of the scolex. Otobothrium crenacolle is readily distinguished by its larger bothrial pits. The metabasal armature begins on either the bothrial or internal surface of the tentacle depending upon the species.